The motivational needs of entrepreneurship in Malacca - Ho, Tiong Keng (Universiti Malaysia Sarawak, UNIMAS, 2006)
This research is conducted to examine the motives that stimulate Malacca people to establish business and it is based on the motivational needs of achievement, affiliation and power as proposed by McClelland (1961). This research aims to understand the typical profile of Malacca entrepreneurs and identify the gender differences of entrepreneurs in terms of three motivational needs. Moreover, the extent of three psychological needs that differs in between the entrepreneurs and employees would be identified in order to study their psychological needs in business ownership. The significant of entrepreneurs’ demographics in affecting the three motivational needs of entrepreneurs would also be identified. Hence, a survey is carried out at high traffic areas for a time period of three weeks starting from 28/11/05 till 18/12/05. In the end, the findings of the research conclude that female entrepreneurs are motivated by a higher need for achievement and power than female employees. However, female entrepreneurs are not motivated by a lower “need for affiliation” than female employees. Meanwhile, male entrepreneurs are motivated by a higher need for achievement and power as well as lower need for affiliation than male employees. In addition, female entrepreneurs are not motivated by a higher need for achievement and power than male entrepreneurs. However, female entrepreneurs are motivated by a lower need for affiliation than male entrepreneurs. Finally, level of education is significant in affecting the three motivational needs and in addition, gender is significant in affecting need for affiliation.